BETWEEN RECOGNITION AND REDISTRIBUTION: Rethinking Public Policies for Women's Protection Through the Lens of Legal Effectiveness (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This article analyzes public policies for the protection of women from the perspective of the theories of Nancy Fraser, Miguel Reale, and contemporary feminist authors. The research highlights the importance of integrating recognition and redistribution in the formulation of effective strategies to combat gender-based violence. Using a qualitative approach based on documentary and bibliographic analysis, the study examines how policies that reconcile cultural, economic, and institutional justice can promote greater equity and social participation. The reflections presented point to the need for a transformative model that expands women's protection and rights. Keywords: Violência contra a mulher, reconhecimento, redistribuição, políticas públicas, justiça social, equidade.